Projetando para sensações, construindo atmosferas: a imersão corpórea na experiência museal - Silva, Mariana de Queiroz (2020)
Based on the primacy of psychological analysis of the lived experience, an architecture that explores phenomenological principles was adopted by architects in a moment of transformation, when professionals were driven to create spaces that favor a more personal and sensitive human experience according to the particularities of individuals; to places that rescue the history/memory of the space and the people through the valorization of the genius loci and that understands the body as the means for the multisensory apprehension of the space. In this context, the properties of the materials, architectural geometric shapes, and the way in which immaterial factors such as lighting, temperature, noise, and even odors are manipulated should be able to create a more intimate bond and evoke feelings and emotions in its users. Taking as the object of study an architectural shape and the spatial perception in the Jewish Museum of Berlin, designed by Daniel Libeskind, and the Museum of Ocean and Surf, designed by architects Steven Holl and Solange Fabião, this research aims to understand the phenomenological experience in museums from the analysis of the combination of natural phenomena (light and shadow, water, wind, temperature) and the architectural geometric shapes used in the projects. Specific objectives are (1) to interpret the presence of phenomenology in architecture; (2) identify the presence of cultural, environmental, and sensory aspects in the creation of architectural atmospheres of the case studies; and, mainly, (3) identify the correlation between geometric shapes and the emotions and feelings that users have within the building. For this, the thesis is divided into three stages: (i) the theoretical approach through the literature review relevant to the theme; (ii) analysis of the buildings based on the elements covered in chapters 02 and 03, as well as an appreciation of the architects' discourse; (iii) the experience of the space, when the author visited the buildings mentioned in order to identify how the construction contributed to the sensations felt. The results showed that in the chosen cases, the sensations are the result of both spatial aspects and the expography itself and the interactive resources current in the spaces.